2010
DOI: 10.1002/chem.201000111
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Singlet‐Oxygen and Superoxide‐Ion Generation by Porphyrins and Bacteriochlorins and their Implications in Photodynamic Therapy

Abstract: New halogenated and sulfonated bacteriochlorins and their analogous porphyrins are employed as photosensitizers of singlet oxygen and the superoxide ion. The mechanisms of energy and electron transfer are clarified and the rates are measured. The intermediacy of a charge-transfer (CT) complex is proved for bacteriochlorins, but excluded for porphyrins. The energies of the intermediates and the rates of their interconversions are measured, and are used to obtain the efficiencies of all the processes. The mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(136 citation statements)
references
References 56 publications
7
127
0
Order By: Relevance
“…[44] The quenching rate constants measured for bacteriochlorins are faster, providing evidence for the presence of charge-transfer interactions, as detailed in the literature. [42] These values are consistent with diffusion limited energy transfer from the triplet state of the sensitizer to molecular oxygen. [54] Singlet oxygen quantum yields were obtained from phosphorescence at 1270 nm using the method described below.…”
Section: Spectroscopic and Photophysical Characteristics Of The Sensisupporting
confidence: 69%
See 2 more Smart Citations
“…[44] The quenching rate constants measured for bacteriochlorins are faster, providing evidence for the presence of charge-transfer interactions, as detailed in the literature. [42] These values are consistent with diffusion limited energy transfer from the triplet state of the sensitizer to molecular oxygen. [54] Singlet oxygen quantum yields were obtained from phosphorescence at 1270 nm using the method described below.…”
Section: Spectroscopic and Photophysical Characteristics Of The Sensisupporting
confidence: 69%
“…The lower F D observed for the bacteriochlorin is precedented in related bacteriochlorins [38] and is attributed to the involvement of charge-transfer in the mechanism of energy transfer to molecular oxygen that may lead to the formation of the superoxide ion. [42] Spectroscopic evidence for electron transfer from electronically excited (5,10,15,20-tetrakis(2,6-dichloro-5-sulfophenyl)bacteriochlorin to molecular oxygen in dimethylsulfoxide, resulting in the formation of O 2 À C, was recently described using a spin trap. [42] Cytotoxicity assay…”
Section: Spectroscopic and Photophysical Characteristics Of The Sensimentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have suggested that it depends on the structure and concentration of the PS and the concentration of O 2 . [24][25][26] The effects of PDT on tumor tissues are now known to be due to four mechanisms: (1) direct cytotoxicity, (2) vascular injury, (3) inflammatory response, and (4) host immune response 27,28) (Fig. 5).…”
Section: Stimuli-responsive Systems Of Therapeuticsmentioning
confidence: 99%
“…The enhanced phototoxicity of the bacteriochlorin was attributed, in part, to the generation superoxide ion (O 2 C À ) by electron transfer in competition with the generation of singlet oxygen ( 1 O 2 ) by energy transfer. [29] The higher phototoxicity of the bacteriochlorin motivated its choice for the first in vivo studies with this series of compounds. [25] The biodistribution of TCPBSO 3 H in DBA mice bearing S91 tumors revealed that the tumor-to-skin ratio increases with time, reaching approximately 10 in the first 48 h post-i.v.…”
Section: à6mentioning
confidence: 99%